Divergencia y convergencia regional en el Perú: 1978-1 992 - Gonzales de Olarte, Efraín (2004)
This is a paper on the Regional Convergente Hypothesis, applied to the Peruvian caseduring the 1978-1992 period. The research considers an important element, generallyneglected by studies on economic growth: the spatial organization of the economy inregions. For that purpose, the empirical analysis has used spatial economic tools,applied to a panel data model with fixed effects and SAR (1) errors.The findings show the absence of trends towards conditional convergence, whichmeans that the Peruvian Departments as such lack steady growth paths in the mediumtem. The data also show that during #e hyperinflation and structural adjustment periods,the less developed Departments presented slow down factors. Finally, the analysicshows that the public expenditure plays an important compensatory role of thedecelerating and accelerating forces of growth, and that its impact is more favorable togrowth when regions are considered, instead of the Departments. These results reinforcethe idea that integration of the Departments into regions is necessary.